Gendered-Traits for rice product profiles, Côte d’Ivoire - N'Dour, M.; Ly, C.O.; Kokola, J.A. (Africa Rice Center, 2023)
A qualitative survey during 26 October to 06 November 2023 in Côte d'Ivoire, focusing on gender characteristics for rice product profiles within the framework of the MI initiative. The activities initially consisted of varietal characterization studies across Africa, conducted within the CGIAR, which identified 9 target product profiles for the improvement of rice varietal selection. A comprehensive literature review was conducted to identify traits that are complementary to the traits constructed in the TPP and how they are interpreted according to the needs of women, men and other key stakeholders. The comprehensive review included publications, PVS reports, other thematic reports, databases and peer-reviewed articles. The different ecologies and the whole technical process from the production to the processing and consumption of the rice were taken into account. The review also took into account the information provided by women in this literary journal. This research was complemented by a qualitative field study based on previous socio-economic, agronomic, market and other participatory studies carried out in the selected countries, including Côte d'Ivoire. It led, through focus groups held in different areas and ecologies of the country, to the identification of important traits for the different actors, especially for women, highlighting their needs in terms of rice varietal breeding program. The results of this study will allow a better consideration of their characteristic preferences in order to facilitate the adoption of improved varieties.